Medical Imaging 2016: Image-Guided Procedures, Robotic Interventions, and Modeling 2016
DOI: 10.1117/12.2216059
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive tools pipeline for assistance of mitral valve surgery

Abstract: For cardiac surgeons, mitral valve reconstruction (MVR) surgery is a highly demanding procedure, where an artificial annuloplasty ring is implanted onto the mitral valve annulus to re-enable the valve's proper closing functionality. For a successful operation the surgeon has to keep track of a variety of relevant impact factors, such as patient-individual medical history records, valve geometries, or tissue properties of the surgical target, and thereon-based deduce type and size of the bestsuitable ring prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Medical imaging databases such as XNAT are developed for imaging upload and information extraction. 14 For all the papers in this review, an overwhelming 23 (58%) CSTs used X-ray-based images such as computed tomography (CT) as their primary data source. 6 (15%) CSTs adopted MRI as their data source while another 6(15%) CSTs used ultrasound; however, they are not as common as the CT scans due to a variety of different reasons relating to costs and accuracy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Medical imaging databases such as XNAT are developed for imaging upload and information extraction. 14 For all the papers in this review, an overwhelming 23 (58%) CSTs used X-ray-based images such as computed tomography (CT) as their primary data source. 6 (15%) CSTs adopted MRI as their data source while another 6(15%) CSTs used ultrasound; however, they are not as common as the CT scans due to a variety of different reasons relating to costs and accuracy.…”
Section: Resultsmentioning
confidence: 99%
“… 20 , 21 Interestingly, contradictive reports were observed between 2 studies; Dixon reported a decrease in recognition while Marcus reported an increase in recognition. 20 , 22 Additionally, 2 studies involving a surgical predictive tool reported numerical values assessing the efficacy of their algorithm 14 , 23 ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Technology to automate performance of some surgical activities under supervision is in its nascent stages, with the current work focused on automation of simple tasks such as suturing and knot-tying [59], [60]. Enhanced technologies that either guide or inform surgeons include augmented visualization to guide the operating surgeon or robot-assisted navigation [61], [62], [63], [64], process or workflow analyses for resource management [65], context-aware medical devices [66], surgical trajectory planning [67], automated control of environment in the operating room [68], simulation of SPMs [55], and other virtual reality and cognitive tools for surgical planning [69], [70]. Data analytics that enable technology for such context-aware assistance to surgical care providers are reviewed in detail elsewhere [71].…”
Section: Examples and Potential Applicationsmentioning
confidence: 99%